Histopathologic findings induced by using contaminated food with Mycotoxins - M Asadi (Babol University of Medical Sciences, 2001)
Objective: Aspergillus fumigatus and aspergillus flavus were known as pathogenic fungi and their conidia and metabolites (Mycotoxins) cause diseases in many living organisms. Aspergillus fumigatus mostly grow on the stored cereals and aspergillus flavus usually grow on the rotten vegetables and Mycotoxin was produced by them. This study was done to survey long-term effects of contaminated food by fungi in rats. Methods: In this study, Wistar rats were divided into three groups: One group was fed with ordinary food (Plate) as a control, and two experimental groups were fed with a contaminated food by asp.fumigatus and asp.flavus for one and three months respectively. In all groups intestine, lung and kidney biopsy were drawn and surveyed for microscopic investigation. Findings: Histopathologic findings in experimental groups were as follows: Congestion in nephrons and intratubular spaces and collape glomerulus in kidney, spreading of lymphatic nodes and aggregation of lymphatic cells in pulmonary parenchyma and aggregation of lymphatic cells in intestinal lamina propria. Conclusion: Findings showed the destructive effects of asp.fumigatus and asp.flavus on various organs. Since the molded food is commonly used in animal husbandry, the inspection and prevention of this matter is necessary. On the other hand, giving public awareness regarding how to keep food out of the fungi would be helpful.